2005
DOI: 10.18806/tesl.v23i1.76
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' and Students' Beliefs About Responding to ESL Writing: A Case Study

Abstract: The purpose of this study was to investigate ESL instructors' feedback techniques and the rationales behind these techniques, to explore ESL students' beliefs about the relative effectiveness of various types of feedback, and to compare students' beliefs with those of their instructors. A university-level ESL instructor and two of her students participated in this case study. Data were collected by think-aloud protocols and semistructured interviews, and results revealed four major categories: (a) types of fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 24 publications
4
51
1
5
Order By: Relevance
“…For instance, in their examination of ESL learners' metalinguistic reflections, Simard et al (2015) found that some error corrections may lead to learners' erroneous hypotheses about the intent of their instructors. Similar results are also reported in other studies (e.g., Brown 2009;Diab 2005;Montgomery and Baker 2007). One recommendation offered by these studies is that a shared understanding of WCF needs to be reached among students and instructors.…”
Section: Review Of Literaturesupporting
confidence: 88%
See 1 more Smart Citation
“…For instance, in their examination of ESL learners' metalinguistic reflections, Simard et al (2015) found that some error corrections may lead to learners' erroneous hypotheses about the intent of their instructors. Similar results are also reported in other studies (e.g., Brown 2009;Diab 2005;Montgomery and Baker 2007). One recommendation offered by these studies is that a shared understanding of WCF needs to be reached among students and instructors.…”
Section: Review Of Literaturesupporting
confidence: 88%
“…One particular area that has attracted increasing attention is how students and teachers perceive the usefulness of WCF (e.g., Amrhein and Nassaji 2010;Brown 2009;Diab 2005;Karim and Nassaji 2015;Lee 2008;Montgomery and Baker 2007;Simard et al 2015). Learner perception presents a key variable influencing the role of WCF for two major reasons.…”
mentioning
confidence: 99%
“…A new trend in corrective feedback research, however, has been the study of students' and teachers' perceptions and beliefs about corrective feedback (Baker, 2007;Brown, 2009;Diab, 2005;Ferris & Roberts, 2001;Hyland, 2003;Jean & Simard, 2011;Lasagabaster & Sierra, 2005;Lee, 2013;Loewen et al, 2009;Plonsky & Mills, 2006;Schulz, 2001;1996). What makes research into this area worthwhile for language pedagogy is the necessity of a relative match between the CF perceptions and preferences of students and teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Truscott, 1996;Ferris and Roberts, 2001;F. Hyland, 2003;Bitchener, Young & Cameron, 2005;Diab, 2005b;Rahimi, 2009), in EFL Arab context such issue has not been addressed adequately.…”
mentioning
confidence: 99%